Screen conformal half-lightlike submanifolds - K. L. Duggal; B. Sahin (International Journal of Mathematics and Mathematical Sciences)
We study some properties of a half-lightlike submanifold M, of a semi-Riemannian manifold, whose shape operator is conformal to the shape operator of its screen distribution. We show that any screen distribution S(TM) of M is integrable and the geometry of M has a close relation with the nondegenerate geometry of a leaf of S(TM). We prove some results on symmetric induced Ricci tensor and null sectional curvature of this class.